A novel structure of hybrid active power filter based on voltage‐current source converter (VCSC‐HAPF). (16th November 2016) - Zafari, A.; Jazaeri, M.
Summary: This article establishes a new parallel hybrid active power filter that is elaborated on the joint operation of voltage and current source converters. The idea is in fact combining a voltage source converter (VSC) and a current source converter (CSC) in parallel to form a hybrid scheme that aggregates the benefits of both converters and does not have drawbacks of each one of them. It is conceptually discussed that when low‐frequency components in the reference current are conducted to the CSC and high‐frequency components are devoted to the VSC, then significant reductions can be obtained in the sizes of the hybrid compensator's elements. However, the merit of the proposed scheme is dependent on separation frequency. The idea is then supported by mathematical descriptions and next validated by a series numerical simulation in Matlab/Simulink environment. The performance of the proposed hybrid scheme is successfully examined in a typical distribution network and also compared with a CSC and/or VSC alone.